Analysis of biosafety of passengers transportation by air transport - Dekar, D.O.; Gorupa, V.V. (Problems of Environmental Biotechnology, 2021)
The problem of the spread of pathogenic microorganisms on board of passenger plane is considered. It is proved that the air conditioning system of the aircraft and the organization of air flows in the cabin are the main factors in the infection of passengers during the flight. Recommendations for changing the direction of airflow to prevent infection of passengers during the flight are presented and substantiated.